(untitled) (Research, Society and Development, 2022)
Introduction: The use of hydroxyapatite-based cements in dental and bone tissue regeneration procedures has shown favorable results. However, structural fragility and lower levels of radiopacity at clinical evaluation make it difficult to use in direct clinical procedures. Objective: This study aimed to synthesize a new cement with properties to be considered for use in dental repair procedures using hydroxyapatite and a hydrogel, with the addition of bismuth oxide as a radiopacifying agent. Methodology: The materials were obtained by a mixture of hydroxyapatite produced by the precipitation method, a hydrogel with carboxymethylcellulose and calcium silicate and bismuth oxide. The products were characterized by X-ray diffraction, Fourrier transform X-ray fluorescence, scanning electron microscopy, setting time, pH and radiographic appearance. Data were analyzed using Jamovi® software version 1.6 to calculate absolute frequencies, as well as measures of central tendency and variability. Results: The proposed cements obtained presented phase compositions without alterations in the composites, with a nanometric porous structure. Basic pH contributes to its bioactivity and antimicrobial action. The drying time of the proposed cements was prolonged. From the radiographs, the cement containing bismuth oxide was radiopaque when compared to the cement without this component. Conclusion: A new dental cement based on hydroxyapatite and bismuth oxide was obtained, homogeneous, with satisfactory radiopacity property, enabling its analysis through radiographic examinations.